PELATIHAN PEMBUATAN ALAT DETEKSI SEDERHANA DAN IDENTIFIKASI BORAKS DAN FORMALIN PADA MAKANAN KELURAHAN AIR HITAM - Wahid, Rifky Saldi A. (Jurnal Pengabdian Masyarakat Teknologi Laboratorium Medik Borneo, 2022)
Food safety is one of the main health issues in Indonesia that needs to be handled properly by the government, producers and consumers (community). To get the food as desired, then in the manufacturing process is done with the addition of food additives or called food additives. The function of providing food additives is to prevent or slow down food spoilage, extend fresh shelf life or prevent insect spoilage in foodstuffs that are stored in large quantities. Formalin and Borax have bad side effects on health. The use of food can cause poisoning in the human body, namely abdominal pain accompanied by vomiting, nervous system or circulatory failure so it can be carcinogenic. To determine the presence or absence of borax in food, laboratory tests must be carried out. This community service aims to provide health education and manufacture and training in making simple tools to detect formalin and borax in food in Air Hitam Village.